Musculoskeletal Manifestations of Rare Lymphoproliferative Neoplasms: A Retrospective Case Report of Four Cases - Meagan E Tibbo; Max C Baron; Alina Syros; Jacob Cohen; H Thomas Temple; Brooke Crawford (Journal of Orthopaedic Case Reports)
Introduction: Lymphoproliferative neoplasms (LPNs) can lead to diverse musculoskeletal manifestations, presenting diagnostic challenges due to their rarity and atypical clinical features. Case Report: This retrospective case series, conducted at a tertiary care hospital, examines four patients with rare LPNs – Rosai–Dorfman disease, Kimura disease, and Castleman disease – initially misdiagnosed as nonneoplastic conditions. The study aims to underscore the importance of histopathological evaluation in achieving accurate diagnoses and initiating timely management. Results reveal diagnostic complexities, with an average of 2.5 biopsies required for accurate diagnosis. Conclusions: In-depth case discussions highlight the unique challenges and treatment strategies for each LPN. The central theme emphasizes the critical role of histopathology in distinguishing these rare LPNs from more common musculoskeletal disorders, guiding appropriate therapeutic interventions, and optimizing patient outcomes. These cases serve as poignant examples of the diagnostic pitfalls encountered by clinicians when faced with rare LPNs, reinforcing the necessity of a nuanced approach and collaboration between clinicians and pathologists in achieving accurate diagnoses.